Regional inequality of socioeconomic status and the prevalence of hypertension between rural and urban areas. (3rd October 2022) - Cho, D; Ha, M C; Jo, H R; Kang, S H
Abstract: Background: Lower socioeconomic status (SES) is associated with greater burdens of cardiovascular disease in a community. The regional disparity of SES may result in an uneven distribution of hypertension (HTN) by a region. This study aims to analyze the regional disparity in the SES and HTN burden between rural and urban areas of the Korea. Methods: We used data from the Korea National Health and Nutrition Examination Survey (KNHANES) V (2010–2012), VI (2013–2015), and VII (201–2018). We analyzed 11, 206 and 1739 subjects from Seoul metropolitan and rural area (Gangwon province), respectively. We compared socioeconomic characteristics, the distribution of HTN between two regions. Finally, we performed a multivariate logistic regression adjusting for traditional CV risk factors and SES status to examine differences in the prevalence of HTN. Results: Subjects in Gangwon province were older than Seoul (54.6±0.4 vs 49.4±0.2 years old, p<0.001). The proportions of subjects with low economic status and low education level were significantly higher in Gangwon province compared to Seoul (low economic status; 25.6 vs 14.4%, p<0.001, low education level; 35.3 vs 16.5%, p<0.001). Mean systolic blood pressure (SBP) was higher in Gangwon compared to Seoul (121.6±0.4 vs 118.1±0.2 mmHg, p<0.001). In the longitudinal trend from KNHANES V to VII, the difference of SBP between the two regions increased (Figure). The age-matched prevalence of HTN was significantly higher in Gangwon compared to Seoul (23.8 vs 21.6%, p<0.05), and the difference of prevalence of HTN by regions longitudinally increased (Figure). In the univariate analysis, the residency in Gangwon was associated with the presence of HTN (reference: Seoul, OR=1.63; 95% CI: 1.45–1.83). In the multivariate logistic regression model, the residency in Gangwon was not associated, however, low economic status and low education level were significantly associated with the presence of HTN (economic status, OR=1.39; 95% CI: 1.17–1.67, education level, OR=1.88; 95% CI: 1.57–2.24). Conclusion: The SES status was lower and the prevalence of HTN was higher in Gangwon compared to Seoul. The burden of HTN longitudinally increased in Gangwon, but not in Seoul. The poor SES was significantly associated with HTN. It suggests that the inequalities of SES in Gangwon may contribute to the increasing prevalence of HTN. The regional and individual disparity of SES should be considered in the establishment of public health strategies for HTN. Funding Acknowledgement: Type of funding sources: None.